Method for manufacturing a recycled cathode active material
Patent Information
- Application Number
- CN202580022546.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-03-06
- Publication Date
- 2026-10-27
AI Technical Summary
根据本公开,能够提供能够抑制由高温的二氧化碳引起的正极活性物质的劣化的再循环正极活性物质的制造方法。
Abstract
Description
Technical Field
[0001] This disclosure relates to a method for manufacturing a recyclable positive electrode active material. Background Technology
[0002] The positive electrode active material of batteries contains rare metals such as cobalt, nickel, manganese, and lithium. This is particularly true in the positive electrode active material of non-aqueous electrolyte secondary batteries, where compounds with these rare metals as their main components are utilized. To conserve rare metal resources, methods for reprocessing rare metals from waste secondary batteries are needed.
[0003] For example, Patent Document 1 discloses a method in which a positive electrode composite is mixed with an activating agent containing an alkali metal compound, the mixture is heated to decompose the binder, and the decomposed products and activating agent are removed using water or the like to recover the positive electrode active material. This method does not use organic solvents, making it cost-effective from the perspective of directly recovering the positive electrode active material from battery waste.
[0004] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2012-186150 Summary of the Invention
[0005] The problem that the invention aims to solve When recycling the positive electrode active material in the positive electrode composite, the positive electrode composite is mixed with an activating agent, and the resulting mixture is heated. When the mixture is heated, the carbon-containing components in the mixture (e.g., carbon-containing materials contained in the positive electrode composite) are burned, producing carbon dioxide. Furthermore, the produced carbon dioxide is heated to a high temperature in the furnace; however, it is known that if the high-temperature carbon dioxide comes into contact with the positive electrode active material in the mixture, it may cause degradation of the positive electrode active material.
[0006] Therefore, the purpose of this disclosure is to provide a method for manufacturing a recycleable positive electrode active material that can suppress the degradation of the positive electrode active material caused by high-temperature carbon dioxide.
[0007] Methods for solving problems This disclosure includes, for example, the following [1] to [9].
[0008] [1] A method for manufacturing a recyclable positive electrode active material, comprising the following steps.
[0009] (1) A process of mixing a positive electrode composite containing a positive electrode active material and a carbon-containing material with an activating agent containing one or more alkali metal compounds to obtain a mixture; (2) The process of transferring the above mixture into a heating furnace, heating the above mixture, and removing the carbon dioxide generated by heating the above carbon-containing material from the heating furnace to obtain the heated mixture; (3) The process of recovering the heated positive electrode active material from the above heated mixture.
[0010] [2] According to the manufacturing method described in [1], the carbon dioxide is removed by gas injection.
[0011] [3] According to the manufacturing method described in [2], in the above-mentioned step (2), when comparing the carbon dioxide concentration in the gas to be supplied to the above-mentioned heating furnace with the carbon dioxide concentration in the gas exhausted from the above-mentioned heating furnace, the carbon dioxide concentration in the gas exhausted from the above-mentioned heating furnace is higher.
[0012] [4] The manufacturing method according to any one of [1] to [3], wherein the carbon dioxide is removed by passing it through a carbon dioxide adsorbent.
[0013] [5] The manufacturing method according to any one of [1] to [4], wherein in the above-mentioned step (2), the above-mentioned mixture is heated to a temperature above the melting start temperature of the above-mentioned activating agent.
[0014] [6] The manufacturing method according to any one of [1] to [4], wherein in the above-mentioned step (2), the above-mentioned mixture is heated to a temperature lower than the melting start temperature of the above-mentioned activating agent.
[0015] [7] The manufacturing method according to any one of [1] to [6], wherein the above-mentioned positive electrode active material comprises a lithium compound.
[0016] [8] The manufacturing method according to any one of [1] to [7], wherein the above-mentioned positive electrode active material comprises a composite oxide containing at least one element selected from the following group 1 and at least one element selected from the following group 2.
[0017] Group 1 elements: Ni, Co, Mn, Fe, Al, and P Group 2 elements: Li, Na, K, Ca, Sr, Ba, and Mg [9] The manufacturing method according to any one of [1] to [8], wherein the activating agent comprises at least one compound selected from the group consisting of potassium compounds and sodium compounds.
[0018] Invention Effects According to this disclosure, a method for manufacturing a recycleable positive electrode active material is provided, which can suppress the degradation of the positive electrode active material caused by high-temperature carbon dioxide. Detailed Implementation
[0019] (Method for manufacturing recycled positive electrode active material) The following describes the manufacturing method of the positive electrode active material involved in recycling.
[0020] One embodiment of the present disclosure provides a method for manufacturing a recyclable positive electrode active material, which includes the following steps.
[0021] Process (1): A process of mixing a positive electrode composite containing positive electrode active material and carbon-containing material with an activating agent containing one or more alkali metal compounds to obtain a mixture; Step (2): The mixture is placed into a heating furnace, and while the mixture is heated, the carbon dioxide generated by heating the carbon-containing material is removed from the heating furnace to obtain the heated mixture. Process (3): The process of recovering the heated positive electrode active material from the heated mixture.
[0022] According to one embodiment of the method for manufacturing a recyclable positive electrode active material, when heating a mixture of positive electrode composite material and activating agent in a furnace, carbon dioxide generated by heating carbon-containing materials (e.g., binders, carbon-based conductive materials) is removed from the furnace while the mixture is being heated. This prevents carbon dioxide from accumulating in the furnace, thus suppressing excessively high carbon dioxide concentrations within the furnace. Furthermore, preventing carbon dioxide accumulating in the furnace also prevents the continuous heating of carbon dioxide to high temperatures. Through these measures, according to this disclosure, the degradation of the positive electrode active material caused by high-temperature carbon dioxide can be suppressed. However, the mechanism of this disclosure is not limited to the above.
[0023] The following is a detailed description of each process.
[0024] Previous process (A): Preparation of positive electrode material First, prepare a positive electrode composite material containing positive electrode active material and carbon-containing material.
[0025] [Positive electrode active material] Examples of positive electrode active materials include composite compounds containing one or more of the following as constituent elements: lithium, oxygen, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, yttrium, niobium, molybdenum, silver, indium, and tungsten. Positive electrode active materials can also be substances containing lithium compounds.
[0026] Positive electrode active materials can consist of a single compound or multiple compounds.
[0027] The positive electrode active material preferably contains a composite oxide comprising at least one element selected from the following element group 1 and at least one element selected from the following element group 2.
[0028] Element group 1: Ni, Co, Mn, Fe, Al and P Element group 2: Li, Na, K, Ca, Sr, Ba and Mg The positive electrode active material preferably contains a compound represented by the following formula (A).
[0029] Li 1+a M 2 b M 1 M T c O 2+d X e (A) wherein, M 2 represents at least one element selected from the group consisting of Na, K, Ca, Sr, Ba and Mg, M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al and P, M T represents at least one element selected from the group consisting of transition metal elements other than Ni, Co, Mn and Fe, X represents at least one element selected from the group consisting of nonmetallic elements other than O and P, which satisfies -0.4<a<1.5, 0≤b<0.5, 0≤c<0.5, -0.5<d<1.5 and 0≤e<0.5.
[0030] M T is preferably at least one element selected from the group consisting of Cu, Ti, Mg, Al, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, Ca, Sr, Ba, Ge, Cr, Sc, Y, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd and In. Examples of X include F, S, Cl, Br, I, Se, Te, N and the like.
[0031] The positive electrode active material preferably contains a composite oxide at least comprising Li and Ni.
[0032] In the positive electrode active material, M 1 has a Ni molar fraction of preferably 0.3 to 0.95.
[0033] The crystal structure of the positive electrode active material (for example, the composite oxide) is not particularly limited, but is preferably a layered structure, more preferably a hexagonal or monoclinic crystal structure.
[0034] The hexagonal crystal structure is assigned to the following crystal groups: P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P Any space group formed by the group consisting of P62, P64, P63, P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc.
[0035] The crystal structure of the monoclinic crystal form belongs to any one of the space groups selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c.
[0036] The crystal structure of the positive electrode active material preferably belongs to the space group R-3m contained in the hexagonal crystal structure or the space group C2 / m contained in the monoclinic crystal structure.
[0037] The crystal structure of the positive electrode active material can be identified by the powder X-ray diffraction pattern obtained by powder X-ray diffraction using CuKα rays as the radiation source.
[0038] There is no particular limitation on the particle size of the positive electrode active material in the positive electrode composite, but it can be from 0.001 to 100 μm. The particle size distribution of the positive electrode active material can be determined using a laser diffraction scattering particle size distribution measuring device (e.g., Malvern Mastersizer 2000). The cumulative particle size distribution curve, which is made into a volume reference from the particle size distribution, can be used to set the value of the particle size (D50) accumulated from the small particle side as the average particle size of the positive electrode active material.
[0039] There are no special restrictions on the content of positive electrode active material in the positive electrode composite.
[0040] [Carbon-containing materials] Examples of carbon-containing materials included in the cathode composite include binders, conductive materials (carbon-based conductive materials), and electrolytes. When a binder is included in the cathode composite, the particles of the positive electrode active material can be bonded together by the binder.
[0041] Examples of adhesives (adhesives before activation treatment) include thermoplastic resins. Specifically, examples include fluoropolymers such as polyvinylidene fluoride (hereinafter, sometimes referred to as "PVdF"), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers; polyolefin resins such as polyethylene and polypropylene; and styrene-butadiene copolymers (SBR). One type of adhesive can be used alone, or two or more can be used in combination.
[0042] There is no particular limitation on the content of binder in the positive electrode composite, but relative to 100 parts by mass of the positive electrode active material, it can be within the following ranges: The binder content can be 0.5 parts by mass or more, 1 part by mass or more, or 2 parts by mass or more. The binder content can be 30 parts by mass or less, 10 parts by mass or less, or 5 parts by mass or less. From these points of view, the binder content can be 0.5 to 30 parts by mass, 1 to 10 parts by mass, 1 to 5 parts by mass, or 2 to 5 parts by mass.
[0043] Specific examples of carbon-based conductive materials include graphite powder (graphite), carbon black (e.g., acetylene black), and fibrous carbon materials (e.g., graphitized carbon fibers and carbon nanotubes).
[0044] Carbon-based conductive materials can be made of a single carbon material or composed of multiple carbon materials.
[0045] The specific surface area of carbon materials used as carbon-based conductive materials can range from 0.1 to 500 m². 2 / g. In this case, carbon-based conductive materials can be made solely from materials with a specific surface area of 30m². 2 It is composed of carbon-based conductive materials with a specific surface area of 30m² or more. 2 Carbon black with a density of 1 g or more can also have a specific surface area of 30 m². 2 Acetylene black of / g or higher. When using an activating agent containing an alkali metal compound with oxidizing power (described later), the oxidation rate of carbon-based conductive materials can be increased, and sometimes even carbon-based conductive materials with small specific surface areas can be oxidized.
[0046] There is no particular limitation on the content of carbon-based conductive material in the positive electrode composite, but relative to 100 parts by mass of the positive electrode active material, it can be within the following ranges: The content of carbon-based conductive material can be 0 parts by mass or more, more than 0 parts by mass, 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more. The content of conductive material can be 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less. From these perspectives, the content of carbon-based conductive material can be 0 to 50 parts by mass, more than 0 parts by mass and less than 40 parts by mass, 1 to 30 parts by mass, 1 to 10 parts by mass, 3 to 20 parts by mass, or 5 to 10 parts by mass.
[0047] In addition to the positive electrode active material and carbon-containing materials, the positive electrode composite material may also contain metallic conductive materials such as metal particles and / or electrolytes. When the positive electrode composite material contains binders and conductive materials, the particles of the positive electrode active material and the conductive materials can be bonded together by the binder. The electrolyte is a component derived from the battery's electrolyte solution and permeated into the positive electrode composite material. The positive electrode composite material may contain fluorine compounds derived from the binder and / or the electrolyte (e.g., the electrolyte in the electrolyte solution).
[0048] Examples of electrolytes include LiPF6, LiBF4, LiClO4, LiN(SO2CF3)2, LiN(SO2F)2, and LiCF3SO3. There are no particular restrictions on the content of electrolytes in the cathode composite material, but it can range from 0.0005 to 7% by mass.
[0049] The cathode material may also contain solvents derived from the electrolyte. Examples of solvents include dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0050] [Recycling of positive electrode materials] Positive electrode composites can be obtained by separating and recycling the positive electrode composite layer from waste positive electrodes that have current collectors and positive electrode composite layer.
[0051] "Waste positive electrode" can refer to positive electrodes recycled from discarded batteries or waste positive electrodes generated during the manufacturing process of positive electrodes or batteries. Discarded batteries can be used batteries or unused but out-of-specification batteries. Waste positive electrodes can be the ends of positive electrodes generated during the battery manufacturing process or out-of-specification positive electrodes. As positive electrode composites, waste positive electrode composites that are not attached to the current collector (waste generated during the positive electrode composite manufacturing process) can also be used.
[0052] The waste positive electrode has a current collector that serves as a metal foil such as aluminum foil or copper foil, and a positive electrode composite layer disposed on the current collector. The positive electrode composite layer can be disposed on one side of the current collector or on both sides.
[0053] Examples of methods for separating the positive electrode composite layer from a waste positive electrode having a current collector and a positive electrode composite layer include methods such as mechanically peeling the positive electrode composite layer from the current collector (e.g., scraping the positive electrode composite layer off the current collector), peeling the positive electrode composite layer from the current collector by impregnating the interface between the current collector and the positive electrode composite layer with a solvent, and separating the positive electrode composite layer by dissolving the current collector using an alkaline or acidic aqueous solution. The preferred method for separating the positive electrode composite layer from a waste positive electrode having a current collector and a positive electrode composite layer is the method of mechanically peeling the positive electrode composite layer from the current collector.
[0054] Previous process (B): Washing process of positive electrode material Next, when the positive electrode material contains an electrolyte, it is suitable to contact the prepared positive electrode material with an electrolyte washing solvent to remove at least a portion of the electrolyte from the positive electrode material. Specifically, the positive electrode material containing a positive electrode active material, a carbon-containing material, etc., is contacted with an electrolyte washing solvent to obtain a slurry containing solid and liquid components, and then the slurry is separated into solid and liquid components.
[0055] Solid-liquid separation is the process of separating a slurry into solid and liquid components. Examples of solid-liquid separation methods include conventionally known methods such as filtration and centrifugation.
[0056] There are no particular restrictions on the electrolyte washing solvent. Examples of electrolyte washing solvents include carbonates such as ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and propylene carbonate; water; ketones such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone; and alcohols such as ethanol, methanol, propanol, and isopropyl alcohol.
[0057] Contact between the electrolyte washing solvent and the positive electrode material can be achieved using a known contact device between powder and liquid (such as a stirring tank).
[0058] In the process of bringing the positive electrode material into contact with the electrolyte washing solvent, it is preferable to stir the positive electrode material and the electrolyte washing solvent to obtain a slurry. The circumferential velocity of the tip of the stirring blade can be 0.1 to 1.0 m / s.
[0059] In the washing process of the cathode material, the solid components can be rinsed after solid-liquid separation. Rinsing involves bringing the electrolyte washing solvent into contact with the solid components again to obtain a slurry, and then separating the slurry into solid and liquid components again. Multiple rinsings can also be performed in the cathode material washing process. The slurry concentration during rinsing can be adjusted arbitrarily. During rinsing, the slurry can also be stirred as described above.
[0060] The above washing process can effectively remove the electrolyte from the cathode material. For example, if electrolyte residue remains, it can sometimes cause the structure of the cathode active material to change from a layered rock salt structure to a spinel structure. However, by removing the electrolyte from the cathode material, this reaction can be suppressed.
[0061] LiPF6+16LiMO2+2O2→6LiF+Li3PO4+8LiM2O4 When the activator contains lithium carbonate, lithium consumption may sometimes occur due to the following reaction, but this reaction can be suppressed by removing the electrolyte from the positive electrode material.
[0062] LiPF6+4Li2CO3→6LiF+Li3PO4+4CO2 The separated solid components can be dried by reducing pressure and / or heating the electrolyte washing solvent, as needed. The heating temperature can be 50–200°C.
[0063] Process (1): Mixing of activating agents Next, the prepared positive electrode material is mixed with an activating agent containing one or more alkaline compounds to obtain a mixture.
[0064] When the positive electrode assembly contains a binder, the particles of the positive electrode active material can be bonded together by the binder. In addition to the positive electrode active material and the binder, the positive electrode assembly may also contain an electrolyte and / or a conductive material. When the positive electrode assembly contains a conductive material, the particles of the positive electrode active material and the conductive material can be bonded together by the binder. The electrolyte is a component derived from the battery's electrolyte solution and impregnated in the positive electrode assembly.
[0065] The mixing method for the positive electrode material and the activating agent can be either dry mixing or wet mixing, or a combination of these methods. There are no particular restrictions on the mixing order of the positive electrode material and the activating agent.
[0066] During mixing, it is preferable to use a mixing device equipped with a mixing medium such as balls to perform a crushing and mixing process, thereby improving mixing efficiency.
[0067] As a mixing method, dry mixing is preferred from the perspective of easier mixing. In dry mixing, V-type mixers, W-type mixers, screw mixers, drum mixers, powder mixers with internal stirring blades, ball mills, vibratory mills, or combinations of these devices can be used.
[0068] As a mixing device used in dry mixing, a powder mixer with internal stirring blades is preferred. Specifically, the Rodier mixer (manufactured by MATSUBO Co., Ltd.) can be cited as an example.
[0069] The following is a detailed description of the activating agent used in this process.
[0070] <Activating agent> The activating agent contains one or more alkali metal compounds. It is preferable that the activating agent contains at least one compound selected from the group consisting of potassium and sodium compounds. Here, potassium and / or sodium are sometimes referred to as alkali metal element X. In addition to potassium and / or sodium compounds, the activating agent may also contain alkali metal compounds including other alkali metals such as Li.
[0071] If the activating agent comes into contact with the positive electrode active material, it can activate the positive electrode active material. In the case of alkali metal compounds in the activating agent, especially those containing molten portions, the contact between the molten portions and the positive electrode active material is enhanced, thereby further promoting the activation of the positive electrode active material.
[0072] In cases where the cathode material contains a binder and / or electrolyte, the cathode material sometimes contains fluorine-containing compounds derived from the binder and / or electrolyte. However, by contacting the fluorine-containing compounds with an activating agent, the fluorine component is stabilized as an alkali metal fluoride, thus suppressing the generation of corrosive gases such as hydrogen fluoride. It should be noted that the generation of hydrogen fluoride is also preferably prevented from the perspective of reducing the activity of the cathode active material.
[0073] The proportion of all alkali metal compounds in the activator is appropriately set considering the type of alkali metal compound and the type of positive electrode active material to be targeted, but it is usually 50% by mass or more relative to the total mass of the activator, preferably 70% by mass or more, and may also be 100% by mass (in the form in which the activator is essentially composed of alkali metal compounds).
[0074] The concentration of at least one alkali metal selected from the group consisting of potassium and sodium in the alkali metal compound can be arbitrarily adjusted from 0 to 100 mol%, but is preferably 10 mol% or more, more preferably 20 mol% or more, more preferably 90 mol% or less, and more preferably 80 mol% or less.
[0075] Alkali metal compounds that can be used as activators include alkali metal hydroxides, borates, carbonates, oxides, peroxides, superoxides, nitrates, phosphates, sulfates, chlorides, vanadates, bromates, molybdates, and tungstates. These compounds can be used alone or in combination as activators.
[0076] Specific examples of preferred alkali metal compounds include hydroxides such as LiOH, NaOH, KOH, RbOH, and CsOH; Boron oxides such as LiBO2, NaBO2, KBO2, RbBO2, and CsBO2; Carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, and CsCO3; Oxides such as Li₂O, Na₂O, K₂O, Rb₂O, and Cs₂O; Peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, and Cs2O2; Superoxides such as LiO2, NaO2, KO2, RbO2, and CsO2; Nitrates such as LiNO3, NaNO3, KNO3, RbNO3, and CsNO3; Phosphates such as Li3PO4, Na3PO4, K3PO4, Rb3PO4, and Cs3PO4; Sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, and Cs2SO4; Chlorides such as LiCl, NaCl, KCl, RbCl, and CsCl; Bromides such as LiBr, NaBr, KBr, RbBr, and CsBr; Vanadates such as LiVO3, NaVO3, KVO3, RbVO3, and CsVO3; Molybdates such as Li₂MoO₄, Na₂MoO₄, K₂MoO₄, Rb₂MoO₄, and CsMoO₄; and Tungstates such as Li2WO4, Na2WO4, K2WO4, Rb2WO4, and CsWO4.
[0077] Here, in order to further improve the activation effect of the positive electrode active material, the activating agent may contain an alkali metal element that is the same as the alkali metal element contained in the positive electrode active material, in addition to being selected from at least one compound in the group consisting of potassium compounds and sodium compounds.
[0078] That is, when the positive electrode active material in the positive electrode composite is a lithium composite oxide, it is suitable that the activating agent, in addition to being selected from at least one compound composed of potassium and sodium compounds, also includes a lithium compound. Preferred lithium compounds include LiOH, LiBO2, Li2CO3, Li2O, Li2O2, LiO2, LiNO3, Li3PO4, Li2SO4, LiCl, LiVO3, LiBr, Li2MoO4, and Li2WO4.
[0079] The activating agent may also contain compounds other than alkali metal compounds, as needed. Examples of compounds other than alkali metal compounds include alkaline earth metal compounds containing elements such as magnesium, calcium, and barium. For the purpose of controlling the melting start temperature of the activating agent, alkaline earth metal compounds are included together with alkali metal compounds in the activating agent.
[0080] Furthermore, the content of compounds other than alkali metal compounds in the activating agent is selected within a range that does not significantly inhibit the effect of the molten alkali metal compounds mentioned above, and may be less than 50% by mass relative to the total mass of the activating agent.
[0081] The amount of activating agent added to the mixture of positive electrode material and activating agent is preferably 0.001 to 100 times, more preferably 0.05 to 1 times, relative to the mass of the positive electrode active material contained in the positive electrode material.
[0082] When the activating agent contains potassium and lithium compounds, from the viewpoint that it is easy to make the charge and discharge characteristics of the battery manufactured using recycled positive electrode active material more similar to those of the battery manufactured using unused positive electrode active material, the ratio of lithium content (mol basis) to potassium content (mol basis) (lithium content / potassium content) can also be 0.01 to 100, 0.1 to 10, or 0.2 to 4.
[0083] When the activating agent contains sodium and lithium compounds, from the viewpoint that it is easy to make the charge and discharge characteristics of batteries manufactured using recycled positive electrode active materials more similar to those of batteries manufactured using unused positive electrode active materials, the ratio of lithium content (mol basis) to sodium content (mol basis) (lithium content / sodium content) can also be 0.01 to 100, 0.1 to 10, or 0.2 to 4.
[0084] When the activator contains a potassium compound, the potassium content (mol basis) in the activator relative to the fluorine content (mol basis) in the cathode material can be, from the viewpoint of making it easier to make the charge-discharge characteristics of a battery manufactured using recycled cathode active material more similar to those of a battery manufactured using unused cathode active material, either 1% or more and less than 500%, 10% or more and less than 400%, 50% or more and less than 300%, 100% or more and less than 250%, or 150% or more and less than 250%.
[0085] When the activator contains a sodium compound, the sodium content (mol basis) in the activator relative to the fluorine content (mol basis) in the positive electrode material can be 1–200%, 10–200%, 50–200%, or 100–200%, 1% or more but less than 150%, 10% or more but less than 150%, 50% or more but less than 150%, or 100% or more but less than 150%, from the viewpoint that it is easier to make the charge-discharge characteristics of a battery manufactured using recycled positive electrode active material more similar to those of a battery manufactured using unused positive electrode active material.
[0086] When the number of moles of the positive electrode active material (e.g., type A) contained in the positive electrode composite is set to 1, the number of moles of the alkali metal compound in the activator in the mixture of the positive electrode composite and the activator can be added in such a way that the number of moles of the alkali metal element is 0.001 to 200 times.
[0087] By appropriately controlling the proportion of activating agents in the mixture, the cost of recovering positive electrode active materials from the positive electrode composite can be reduced, and the oxidation and decomposition processing speed of carbon-containing materials (carbon-based conductive materials, binders, etc.) can be increased. Furthermore, the effect of preventing the generation of corrosive gases during the heating process can be improved, thereby further increasing the discharge capacity of batteries manufactured using the obtained positive electrode active materials.
[0088] Furthermore, at least one of the alkali metal compounds contained in the activating agent is preferably an alkali metal compound that exhibits alkalinity when dissolved in water. When an activating agent containing such an alkali metal compound is dissolved in pure water, the pH of the solution becomes greater than 7. Hereinafter, such an activating agent will sometimes be referred to as an "alkaline activating agent".
[0089] By using an alkaline activating agent, the generation of corrosive gases during the heating process can be further suppressed, thus further increasing the discharge capacity of batteries manufactured using the recovered positive electrode active material. Furthermore, using an alkaline activating agent can also increase the processing speed of carbon-containing materials (carbon-based conductive materials, binders, etc.).
[0090] Alkali metal compounds that exhibit alkalinity when dissolved in water and are included in alkaline activating agents can include alkali metal hydroxides, carbonates, bicarbonates, oxides, peroxides, and superoxides. Specifically, examples of alkaline alkali metal compounds include hydroxides such as LiOH, NaOH, KOH, RbOH, and CsOH; carbonates such as Li₂CO₃, Na₂CO₃, K₂CO₃, RbCO₃, and CsCO₃; bicarbonates such as LiHCO₃, NaHCO₃, KHCO₃, RbHCO₃, and CsHCO₃; oxides such as Li₂O, Na₂O, K₂O, Rb₂O, and Cs₂O; peroxides such as Li₂O₂, Na₂O₂, K₂O₂, Rb₂O₂, and Cs₂O₂; and superoxides such as LiO₂, NaO₂, KO₂, RbO₂, and CsO₂. One or more of these compounds may be included in the activating agent.
[0091] Furthermore, when the conductive material included in the positive electrode composite is a carbon-based conductive material, at least one of the alkali metal compounds contained in the activating agent may also be an alkali metal compound that has oxidizing power to decompose the carbon-based conductive material at the temperature of the heating process. Hereinafter, the activating agent containing such an alkali metal compound is sometimes referred to as an "activating agent with oxidizing power".
[0092] If such an activating agent with oxidizing power is used, it is particularly effective in promoting the oxidation of conductive materials, which are carbon materials, to carbon dioxide, and in promoting the oxidation of binders, which are hydrocarbon materials, to carbon dioxide and water vapor. It can further improve the discharge capacity of batteries manufactured using the obtained positive electrode active material, and sometimes can further improve the effect of preventing the generation of corrosive gases in the heating process.
[0093] Alkali metal compounds with oxidizing power, required for oxidizing carbon-based conductive materials and hydrocarbons into carbon dioxide and water vapor, include alkali metal peroxides, superoxides, nitrates, sulfates, vanadates, and molybdates. One or more of these compounds may be used.
[0094] As alkali metal compounds with oxidizing power, specific examples include peroxides such as Li₂O₂, Na₂O₂, K₂O₂, Rb₂O₂, and Cs₂O₂; nitrates such as LiO₂, NaO₂, KO₂, RbO₂, and CsO₂; sulfates such as Li₂SO₄, Na₂SO₄, K₂SO₄, Rb₂SO₄, and Cs₂SO₄; vanadates such as LiVO₃, NaVO₃, KVO₃, RbVO₃, and CsVO₃; and molybdates such as Li₂MoO₄, Na₂MoO₄, K₂MoO₄, Rb₂MoO₄, and CsMoO₄.
[0095] Details of the oxidizing power of these alkali metal compounds are described in Japanese Patent Application Publication No. 2012-186150.
[0096] From the viewpoint that it is easy to make the charge and discharge characteristics of batteries made using recycled positive electrode active materials more similar to those of batteries made using unused positive electrode active materials, the alkali metal compound may also be a carbonate or sulfate, or at least one selected from the group consisting of Li2CO3, Na2SO4, Na2CO3 and K2CO3.
[0097] Process (2): Heating process Step (2) (heating step) involves taking the mixture obtained in step (1) (hereinafter sometimes referred to as "the mixture before heating") into a heating furnace, heating the mixture before heating, and removing carbon dioxide generated by heating carbon-containing materials (carbon-based conductive materials, binders, etc.) from the heating furnace to obtain a heated mixture. By removing carbon dioxide from the heating furnace, carbon dioxide retention in the heating furnace can be prevented, thus suppressing the high concentration and high temperature of carbon dioxide in the heating furnace.
[0098] Examples of heating furnaces include gas furnaces, electric furnaces, infrared heating furnaces, plasma heat treatment furnaces, heavy oil furnaces, light oil furnaces, hydrogen heat treatment furnaces, induction heating furnaces, vacuum furnaces, salt bath furnaces, tunnel furnaces, roller hearth furnaces, rotary kilns, walking beam furnaces, Carbolite furnaces, mesh belt furnaces, rotary kilns, shuttle kilns, and fluidized bed calcining furnaces. A heating furnace is a space that contains a mixture of materials to be heated; it can be a closed space or an open space with openings for moving the mixture in or out. Heating furnaces can be intermittent furnaces, continuous furnaces, or fluidized bed furnaces. For example, a rotary kiln can be an intermittent rotary kiln or a continuous rotary kiln. When the heating furnace is a continuous furnace, the heating space can also be a gas furnace, electric furnace, infrared heating furnace, plasma heat treatment furnace, heavy oil furnace, light oil furnace, hydrogen heat treatment furnace, induction heating furnace, walking beam furnace, mesh belt furnace, continuous rotary kiln, or continuous shuttle kiln. Fluidized bed calcining furnaces can also be multi-stage, and the temperature can be changed in each stage.
[0099] Carbon dioxide in the heating furnace can also be removed by supplying gas. By supplying gas into the heating furnace, carbon dioxide can be discharged from the furnace, preventing its retention and thus suppressing the high concentration and high temperature of carbon dioxide in the furnace.
[0100] The direction of gas supply within the heating furnace can be determined based on the furnace's structure, the amount of the mixture before heating, and the composition of the gas being supplied. For example, gas can be supplied from the top, side, or bottom of the furnace towards the opposite side. Furthermore, for example, in the case of a continuous furnace, gas supply can be performed in the opposite direction to the direction of travel of the mixture, or perpendicular to the direction of travel of the mixture.
[0101] A continuous furnace has at least an inlet for receiving the mixture before heating and an outlet for removing the mixture after heating. The continuous furnace may also have a gas inlet for supplying gas and an exhaust inlet for discharging carbon dioxide, etc. A continuous furnace may also have multiple gas inlets and multiple exhaust inlets.
[0102] By supplying gas in the opposite direction to the direction of travel of the mixture, the carbon dioxide generated by heating is moved to the inlet side of the continuous furnace. The temperature inside the continuous furnace generally increases from the inlet towards the outlet, thus the inlet side of the continuous furnace becomes a relatively low-temperature region. Therefore, by moving the carbon dioxide generated by heating to the relatively low-temperature inlet side of the continuous furnace, it is possible to prevent the carbon dioxide from becoming high-temperature, thereby further suppressing the contact between high-temperature carbon dioxide and the positive electrode active material.
[0103] Within a continuous furnace, the temperature can also vary along the direction of travel of the mixture. For example, a continuous furnace can also have a region where the temperature gradually increases along the direction of travel of the mixture. The temperature within a continuous furnace (the temperature at any location within the continuous furnace) can, for example, be in the range of room temperature (20°C) to 2000°C.
[0104] A continuous furnace may, for example, have a low-temperature zone near the inlet, a heating zone where the temperature gradually increases from the low-temperature zone towards the outlet, a constant-temperature zone, and a cooling zone where the temperature gradually decreases from the constant-temperature zone towards the outlet. The temperature of each zone and the volume of space occupied by each zone within the continuous furnace can be appropriately determined based on the furnace structure, the amount of mixture before heating, the composition of the supplied gas, and the amount of carbon dioxide produced within the furnace. Gas supply within the continuous furnace can also occur in at least one zone selected from the group consisting of the low-temperature zone, the heating zone, the constant-temperature zone, and the cooling zone.
[0105] In the case of a continuous furnace having gas inlets and / or exhaust ports, the locations of the gas inlets and / or exhaust ports within the continuous furnace can be determined based on the structure of the continuous furnace, the amount of the mixture before heating, the composition of the gas being supplied, the amount of carbon dioxide generated within the continuous furnace, etc. For example, the continuous furnace may have gas inlets arranged along its bottom surface (multiple gas inlets if there are multiple gas inlets) and exhaust ports arranged along its top surface (multiple exhaust ports if there are multiple exhaust ports); alternatively, exhaust ports may be arranged along the bottom surface of the continuous furnace (multiple exhaust ports if there are multiple exhaust ports) and gas inlets arranged along its top surface (multiple gas inlets if there are multiple gas inlets); or gas inlets and exhaust ports may be arranged along the sides of the continuous furnace (multiple gas inlets and multiple exhaust ports if there are multiple gas inlets and multiple exhaust ports). The gas inlets may be arranged opposite to the exhaust ports or not opposite to them.
[0106] Gas supply within a continuous furnace can also be perpendicular to the direction of travel of the mixture within the furnace. Generally, the mixture travels along the bottom, top, or side of the continuous furnace; therefore, gas supply perpendicular to the direction of travel of the mixture within the continuous furnace means supplying gas perpendicular to the bottom, top, or side of the continuous furnace. In the case of supplying gas perpendicular to the direction of travel of the mixture within the continuous furnace, the gas supply may be, for example, from a gas inlet located on the bottom of the continuous furnace toward an exhaust port located on the top of the continuous furnace.
[0107] The gas supplied to the heating furnace is not particularly limited; it can be oxygen-containing gases such as air, or inert gases such as nitrogen and argon. Since the gas supplied to the heating furnace is exhausted along with the carbon dioxide produced inside, the carbon dioxide concentration in the exhaust gas can be higher than that in the gas supplied to the furnace. Alternatively, the exhaust gas can be decarbonized before being reintroduced into the heating furnace.
[0108] Gas supply within the heating furnace can be carried out throughout the furnace or only in a specific area. From the viewpoint of improving carbon dioxide exhaust efficiency and further suppressing the degradation of the positive electrode active material caused by high-temperature carbon dioxide, gas supply within the heating furnace can also be carried out in temperature zones where carbon dioxide production is higher. For example, gas supply can be carried out in zones where the furnace temperature is 300–900°C, 300–700°C, or 300–600°C. Preferably, gas supply within the heating furnace is carried out in a zone below the melting start temperature of the activating agent.
[0109] The flow rate of the gas supplied to the furnace per 1L of heating space can be, for example, 0.001–1.0L / min or 0.01–0.6L / min. The flow rate per 1L of heating space can be appropriately adjusted based on the furnace structure, the amount of mixture before heating, the composition of the supplied gas, and the amount of carbon dioxide generated within the furnace. For example, from the viewpoint of further suppressing the degradation of the positive electrode active material, the flow rate can be increased to further reduce the carbon dioxide concentration within the furnace; conversely, from the viewpoint of improving energy conversion efficiency, the flow rate can be decreased to reduce pressure loss. Furthermore, the flow rate can be adjusted so that the carbon dioxide concentration per 1L of heating space is below a specific value (e.g., below 10% by volume). The flow rate of the gas supplied to the furnace per 1L of heating space can be approximately the same throughout the furnace or vary at different locations within the furnace.
[0110] Carbon dioxide in the heating furnace can also be removed by a carbon dioxide adsorbent (e.g., zeolite 13X). Alternatively, carbon dioxide in the heating furnace can also be removed by a carbon dioxide absorbent. Furthermore, carbon dioxide in the heating furnace can also be removed by a carbon dioxide separation membrane.
[0111] Heating the mixture can also be performed at temperatures above the melting start temperature of the activating agent. The "melting start temperature (Tmp) of the activating agent" refers to the lowest temperature at which a portion of the activating agent exhibits a liquid phase.
[0112] The melting start temperature (Tmp) of the activating agent was determined by differential calorimetry (DTA). Specifically, 5 mg of the mixture before heating was subjected to differential calorimetry (DTA, measurement conditions: heating rate: 10 °C / min), and the temperature at which the DTA signal showed an endothermic peak was taken as the melting start temperature (Tmp).
[0113] The melting start temperature (Tmp) of the activating agent is preferably 700°C or lower, more preferably 600°C or lower. There is no lower limit to the melting start temperature (Tmp) of the activating agent, but it may be, for example, 150°C or higher, 250°C or higher, 350°C or higher, 450°C or higher, or 500°C or higher.
[0114] In step (2), by heating the mixture before heating to a temperature above the melting start temperature (Tmp) of the activating agent, the following effect is achieved: that is, by contacting the molten activating agent with the positive electrode active material, the deterioration of the crystal structure of the positive electrode active material can be suppressed. In addition, the crystal structure can also be repaired.
[0115] By contacting the activating agent in a molten state with carbon-containing materials (carbon-based conductive materials, binders, etc.), the rate of oxidative decomposition of the conductive materials and binders is increased. Furthermore, by contacting the activating agent in a molten state with fluorine compounds derived from the binder and electrolyte, the fluorine component is stabilized as an alkali metal fluoride, preventing the generation of hydrogen fluoride as a corrosive gas and inhibiting the deterioration of the crystal structure of the positive electrode active material.
[0116] Furthermore, when the activator contains the same alkali metal as the positive electrode active material, it can also supply alkali metal that is insufficient relative to the positive electrode active material.
[0117] The highest temperature inside the heating furnace (the highest temperature at any location inside the heating furnace) can, for example, be above the melting start temperature of the activating agent. The highest temperature inside the heating furnace (the highest temperature at any location inside the heating furnace) can, for example, be 300–900°C, 300–700°C, or 300–600°C.
[0118] Furthermore, when only the activator is heated, the melting point of the activator refers to the lowest temperature at which a portion of the activator exhibits a liquid phase. By mixing the positive electrode composite with the activator, the melting start temperature (Tmp) of the activator becomes lower than its melting point.
[0119] The melting point of the activating agent was determined by differential calorimetry (DTA). Specifically, 5 mg of the activating agent was subjected to differential calorimetry (DTA, measurement conditions: heating rate: 10℃ / min), and the temperature at which the DTA signal showed an endothermic peak was taken as the melting point of the activating agent.
[0120] The highest temperature inside the heating furnace (the highest temperature at any location inside the heating furnace) is preferably higher than the melting point of the alkali metal compound contained in the activating agent. The melting point of the alkali metal compound is sometimes lower than the melting point of the individual alkali metal compounds by mixing two or more alkali metal compounds. In cases where the activating agent contains two or more alkali metal compounds, the eutectic point is used as the melting point of the alkali metal compound.
[0121] The residence time of the mixture in the furnace (the time from when the mixture is moved into the furnace to when it is moved out) can also be determined according to the temperature inside the furnace, the amount of mixture before heating, etc. The residence time of the mixture in the furnace can be, for example, 10 minutes to 24 hours.
[0122] The heating time of the mixture above the melting point of the activating agent can be determined based on factors such as the amount of mixture before heating. The heating time above the melting point of the activating agent can range from 1 minute to 24 hours.
[0123] Heating the mixture can also involve heating it to a temperature below the melting start temperature (Tmp) of the activator. By heating the mixture before heating to a temperature below the melting start temperature (Tmp) of the activator, the degradation of the crystal structure of the positive electrode active material caused by heating at high temperatures is suppressed, making it easier to achieve charge-discharge characteristics similar to those of batteries manufactured using unused positive electrode active materials. Furthermore, by heating the mixture before heating together with the activator, a crystal structure repair effect can also be achieved. In this specification, "heating to a temperature below the melting start temperature of the activator" means heating while maintaining a temperature below the melting start temperature of the activator (heating at a holding temperature below the melting start temperature of the activator). Additionally, "heating to a temperature below the melting start temperature of the activator" means heating at a temperature not above the melting start temperature of the activator.
[0124] By contacting the heated activating agent with carbon-containing materials (carbon-based conductive materials, binders, etc.), the rate of oxidative decomposition of the conductive materials and binders is increased. Furthermore, by contacting the heated activating agent with fluorine compounds derived from the binder and electrolyte, the fluorine component is stabilized as an alkali metal fluoride, preventing the generation of hydrogen fluoride as a corrosive gas and inhibiting the deterioration of the crystal structure of the positive electrode active material.
[0125] The highest temperature inside the furnace (the highest temperature at any location inside the furnace) can, for example, be below the melting start temperature of the activating agent. The highest temperature inside the furnace (the highest temperature at any location inside the furnace) can, for example, be 300–600°C, 350–575°C, or 400–550°C.
[0126] The heating time of the mixture below the melting start temperature of the activating agent can be determined based on factors such as the amount of mixture before heating. For example, the heating time below the melting start temperature of the activating agent can range from 1 minute to 24 hours.
[0127] After the heating process, the mixture can be cooled to any temperature as needed (e.g., room temperature (20°C)). By operating in this way, a heated mixture containing the heated positive electrode active material is obtained.
[0128] Process (3): Positive electrode active material recovery process The positive electrode active material recovery process is a process that recovers the heated positive electrode active material from the heated mixture after the heating process in process (2).
[0129] The heated mixture contains, in addition to the heated positive electrode active material, components derived from the activating agent (alkali metal compounds, etc.), undecomposed carbon-containing materials (carbon-based conductive materials, binders, etc.), and undecomposed products of other positive electrode materials. Furthermore, in cases where the positive electrode mixture contains an electrolyte containing fluorine, it may also contain fluorine components derived from the electrolyte.
[0130] Methods for separating and recovering heated positive electrode active material from heated mixtures include solid-liquid separation methods, such as adding solvents like water to the mixture to form a slurry and then separating the solid and liquid components, and gasification separation methods, such as heating the mixture to vaporize and separate the components other than the heated positive electrode active material.
[0131] The solid-liquid separation method will be explained below.
[0132] Process (3a): Solid-liquid separation process Step (3a) involves contacting the heated mixture with a liquid containing water to obtain a slurry containing solid components (the heated mixture or solid components containing the heated positive electrode active material) and liquid components, and then separating the slurry into solid and liquid components.
[0133] In order to separate and recover the heated positive electrode active material from the heated mixture, a liquid containing water is added to the mixture and slurryed, followed by solid-liquid separation to separate the solid and liquid components.
[0134] In the slurry preparation process (a process in which a heated mixture is brought into contact with a liquid containing water to obtain a slurry containing both solid and liquid components), there are no particular restrictions on the type of liquid used, as long as it contains water. The amount of water in the liquid can be 50% by mass or more. To improve the solubility of water-soluble components or to increase the processing speed, components other than water can be added to the liquid to adjust the pH.
[0135] Preferred examples of liquids containing water include pure water and alkaline detergent solutions. Examples of alkaline detergent solutions include aqueous solutions of one or more anhydrous substances and their hydrates selected from the group consisting of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, and ammonium carbonate. Furthermore, ammonia can also be used as a base.
[0136] The resulting slurry comprises a solid component mainly consisting of the heated positive electrode active material, and a liquid component consisting of water-soluble components other than the positive electrode active material. It should be noted that the liquid component includes alkali metal components derived from the activating agent, and / or fluorine components derived from the binder and electrolyte, etc.
[0137] The amount of liquid in contact with the mixture is appropriately determined by taking into account the amounts of the heated positive electrode active material and the water-soluble components other than the positive electrode active material contained in the mixture.
[0138] In step (3a), it is suitable to stir the heated mixture with a liquid containing water to obtain a slurry. This promotes the dissolution of water-soluble components. The circumferential velocity of the tip of the stirring blade is preferably set to 0.1 to 0.9 m / s.
[0139] The slurry obtained in the pulping process is then fed into a solid-liquid separation process. Solid-liquid separation is the operation of separating the slurry into liquid and solid components. Methods for solid-liquid separation can be those already known, such as filtration and centrifugation.
[0140] In step (3a), the obtained solid components may also be rinsed after solid-liquid separation. Rinsing involves bringing a liquid containing water into contact with the obtained solid components again to obtain a slurry, and then separating the slurry into solid and liquid components again. Multiple rinsings may also be performed in step (3a). The slurry concentration during rinsing may also be set to the same as the slurry concentration in the solid-liquid separation step described above.
[0141] In this specification, the positive electrode active material obtained through processes (1) to (3) is referred to as a recycled positive electrode active material. The recycled positive electrode active material obtained through processes (1) to (3) can be suitably used in the manufacture of positive electrodes, etc. The method for manufacturing the recycled positive electrode active material may include additional processes before or after processes (1) to (3). In this specification, the positive electrode active material obtained through additional processes other than processes (1) to (3) is also referred to as a recycled positive electrode active material. Examples of additional processes other than processes (1) to (3) are the preceding processes (A) and (B) performed before process (1), and the following processes (4) and (5) performed after process (3), for example, after process (3a).
[0142] Process (4): Drying process Process (4) is, for example, a process of removing water from solid components by exposing the solid components obtained in process (3a) to a heated and / or depressurized environment.
[0143] In the drying process, the heating temperature is preferably 100°C or higher to remove water. For further thorough water removal, it is preferably set to 150°C or higher. Especially at temperatures above 250°C, the discharge capacity of the battery manufactured using the obtained positive electrode active material is further improved, and therefore preferred. The temperature in the drying process can be fixed, or it can be varied in stages or continuously. The heating temperature range can, for example, be 10°C or higher and below 900°C.
[0144] The pressure range for pressure reduction can be, for example, 1.0 × 10⁻⁶. -10 ~1.0×10 3 Pa.
[0145] Process (5): Annealing (re-firing) process When the activating agent is heated above the melting start temperature, step (5) can also be a step of heat-treating the solid components after step (4) at a temperature below 900°C.
[0146] When the activating agent is heated at a temperature lower than the melting start temperature, step (5) can also be a step in which the solid components after step (4) are heated at a temperature higher than that of step (2). In this case, from the viewpoint of removing impurities by vaporizing components other than the positive electrode active material, and from the viewpoint that it is easier to achieve charge and discharge characteristics similar to those of a battery manufactured using unused positive electrode active material by sufficiently increasing the crystallite size of the positive electrode active material, the temperature at which the heated mixture is heated can be above 700°C, above 750°C, above 800°C, above 850°C, or above 900°C.
[0147] In the annealing process, the heat treatment atmosphere is not particularly limited, but an oxygen-containing atmosphere such as air is suitable. Furthermore, the heat treatment temperature can be 100°C or higher. Additionally, the holding time for heat treatment can be set from 1 minute to 24 hours. In particular, heating at a holding temperature above 350°C for 0.1 hours to 5 hours is suitable.
[0148] The recycled positive electrode active material obtained from battery composites using the method for manufacturing recycled positive electrode active material disclosed herein can be reused in the same way as unused active material. Methods for manufacturing positive electrodes and batteries using recycled positive electrode active material are well known.
[0149] The discharge capacity of the recycled positive electrode active material obtained in the embodiments of this disclosure can be 150 mAh / g or higher.
[0150] Example The present disclosure will now be described in more detail through embodiments, but the present disclosure is not limited to the following embodiments without changing its spirit.
[0151] The determination of the physical properties of the positive electrode active material and the recycle positive electrode active material, and the charge-discharge test based on the battery used as the positive electrode active material, are carried out as follows.
[0152] [Element content] For the solution and the acid solution obtained by dissolving the powder, the content of alkali metal elements contained in the solution and the powder was analyzed using an ICP luminescence analyzer (e.g., SIINano Technology Co., Ltd., SPS3000).
[0153] (See Example 1 for reference) <The Manufacturing of the Positive Electrode> The positive electrode described below is manufactured through the following steps. A mixture is obtained by mixing 92 parts by weight of positive electrode active material (unused positive electrode active material or recycled positive electrode active material), 3 parts by weight of PVdF (binder, manufactured by KUREHA Co., Ltd., part number: #1100), and 5 parts by weight of acetylene black (conductive material, manufactured by Denka Co., Ltd., part number: HS100). As the binder, PVdF is a binder solution obtained by pre-dissolving PVdF in NMP (N-methyl-2-pyrrolidone). A positive electrode composite paste is prepared by kneading the mixture using a rotation-revolution type mixer (THINKY Co., Ltd. ARE-310). NMP is added to adjust the mixture so that the total mass of the positive electrode active material, binder, and conductive material in the positive electrode composite paste is 50% by weight.
[0154] On one side of a 20μm thick aluminum foil 1085 (manufactured by Nippon Foil Co., Ltd.) for the positive electrode current collector of a lithium-ion secondary battery, the mass of the positive electrode active material is 3.0±0.1 mg / cm³. 2 After coating the positive electrode material paste using a specific method, it was vacuum dried at 150°C for 8 hours to obtain the positive electrode. The electrode area of this positive electrode was set to 1.65 cm². 2 .
[0155] <Battery Manufacturing> The coin-shaped battery described later is manufactured through the following steps. A non-aqueous electrolyte secondary battery (coin-shaped battery) is manufactured by combining the above-mentioned positive electrode, electrolyte, separator, and negative electrode. Battery assembly is carried out in a glove box under an argon atmosphere. As the electrolyte, a solution obtained by dissolving LiPF6 in a 30:35:35 (volume ratio) mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate at a ratio of 1.0 mol / L is used. As the separator, a laminated membrane separator obtained by stacking heat-resistant porous layers on a porous membrane (made of polyethylene) is used. As the negative electrode, metallic lithium is used.
[0156] Manufacturing the positive electrode before recycling As the positive electrode active material, it is prepared to have a composition of Li 1.07 Ni 0.47 Mn 0.48 Fe 0.05O2 and a positive electrode active material with a crystal structure of R-3m were used. The aforementioned coin-shaped battery was fabricated using this positive electrode active material (unused positive electrode active material), and the following charge-discharge tests (rate tests) were conducted at 25°C. The 0.2C discharge capacity was 138 mAh / g, and the 5C discharge capacity was 106 mAh / g. A higher 0.2C discharge capacity indicates a higher rated capacity, and a higher 5C discharge capacity indicates better output characteristics.
[0157] (condition) Maximum charging voltage: 4.3V Charging current: 0.2mA / cm 2 Charging time: 8 hours Minimum discharge voltage: 2.5V 0.2C discharge current: 0.2mA / cm 2 5C discharge current: 5.0mA / cm 2 From the positive electrode used in the above-mentioned battery, the electrode assembly is mechanically removed, and the electrode assembly is peeled off from the current collector. In 5g of the electrode assembly removed from the positive electrode, 0.1 mol of K₂CO₃ (relative to 1 mol of the positive electrode active material) and 0.1 mol of Na₂CO₃ (relative to 1 mol of the positive electrode active material) are mixed as activating agents to obtain a mixture (mixture before heating). The melting start temperature of the activating agent is 700°C.
[0158] The mixture before heating is placed in an electric furnace and heated in an air atmosphere at a temperature of 700°C (above the melting start temperature of the activating agent) for 240 minutes.
[0159] The heated mixture was pulverized, distilled water was added, and the mixture was stirred to obtain a slurry. The slurry was filtered to separate the solid and liquid components. The solid component was then recovered and dried to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were identical to those of the unused positive electrode active material. A coin-shaped battery was fabricated using the recycled positive electrode active material, and charge-discharge tests were conducted under the aforementioned conditions at 25°C. The results showed a 0.2C discharge capacity of 135 mAh / g and a 5C discharge capacity of 94 mAh / g, which were identical to the discharge capacity of the coin-shaped battery fabricated using the unused positive electrode active material.
[0160] (See Example 2 for reference) Manufacturing the positive electrode before recycling As the positive electrode active material, it is prepared to be composed of LiNi 0.33Co 0.33 Mn 0.33 O2 and NCM111, a positive electrode active material with a crystal structure of R-3m, were used to fabricate the aforementioned coin-shaped battery. The initial charge capacity was 178.3 mAh / g, and the initial discharge capacity (0.2C) was 163.4 mAh / g. Furthermore, charge-discharge tests (rate tests) were conducted at 25°C, resulting in a 0.2C discharge capacity of 163.1 mAh / g and a 5C discharge capacity of 141.3 mAh / g.
[0161] From the positive electrode produced during the manufacturing of the aforementioned positive electrode, the electrode assembly is mechanically removed, thus separating the electrode assembly from the current collector. In 5g of the electrode assembly removed from the positive electrode, 0.1 mol of Li₂CO₃ (relative to 1 mol of the positive electrode active material) and 0.1 mol of Na₂SO₄ (relative to 1 mol of the positive electrode active material) are mixed as activating agents to obtain a mixture (mixture before heating). The melting start temperature of the activating agent is 510°C.
[0162] Place 30g of the mixture before heating into an electric furnace and heat it in air at a heating rate of 300℃ / h, a heating temperature of 450℃ (lower than the melting start temperature of the activator), and a heating time of 360 minutes.
[0163] The heated mixture was pulverized, distilled water was added, and the mixture was stirred to obtain a slurry. The slurry was then filtered to separate the solid and liquid components. The solid component was then recovered and dried by suction at 100°C for 1 hour.
[0164] The dried solid components were placed in an electric furnace and heated in air at a temperature of 900°C for 60 minutes to obtain the heated recycleable positive electrode active material. The heated recycleable positive electrode active material was then allowed to cool naturally to room temperature (20°C), and the composition, crystal structure, average particle size, and specific surface area of the obtained recycleable positive electrode active material were confirmed to be identical to those of the unused positive electrode active material. Using the recycleable positive electrode active material to fabricate the aforementioned coin-shaped battery, the initial charge capacity was 180.5 mAh / g, and the initial discharge capacity was 161.1 mAh / g. Furthermore, under the same conditions (0.2C discharge capacity and 5C discharge capacity), the initial charge-discharge (rate test) was conducted at 25°C, resulting in an initial discharge capacity of 160.2 mAh / g and a 5C discharge capacity of 133.9 mAh / g.
[0165] (Example 1) The mixture before heating was obtained by operating in the same manner as in Reference Example 1. The obtained mixture before heating was placed in a continuous furnace, where it was heated while air was supplied in the opposite direction to the direction of travel of the mixture before heating. The maximum temperature in the continuous furnace was 700°C (above the melting start temperature of the activating agent), and the mixture before heating was heated under the condition of a residence time of 240 minutes in the continuous furnace. During this process, the carbon-containing materials (PVdF, acetylene black) contained in the mixture before heating generated carbon dioxide through heating, but this was removed from the heating furnace (continuous furnace) by supplying air. Therefore, if the concentration of carbon dioxide in the gas supplied to the heating furnace is compared with the concentration of carbon dioxide in the gas exhausted from the heating furnace, the concentration of carbon dioxide in the gas exhausted from the heating furnace is higher. By supplying air within the heating furnace, the contact between high-temperature carbon dioxide and the positive electrode active material can be suppressed, thus suppressing the degradation of the positive electrode active material caused by high-temperature carbon dioxide.
[0166] The same procedure as in Reference Example 1 was followed to obtain a recycled positive electrode active material from the heated mixture. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were identical to those of the unused positive electrode active material. When the above-described coin-shaped battery was fabricated using the recycled positive electrode active material, and a charge-discharge test was conducted under the above conditions at 25°C, the discharge capacity was identical to that of a coin-shaped battery fabricated using the unused positive electrode active material.
[0167] (Example 2) The mixture before heating was obtained by operating in the same manner as in Reference Example 1. The obtained mixture before heating and the carbon dioxide adsorbent were placed in an electric furnace. The mixture was heated in an air atmosphere at a temperature of 700°C (above the melting point of the activating agent) for 240 minutes. During this process, the carbon-containing materials (PVdF, acetylene black) in the mixture before heating generate carbon dioxide upon heating, but this carbon dioxide is removed from the furnace (electric furnace) by the carbon dioxide adsorbent. The carbon dioxide adsorbent inhibits the contact between high-temperature carbon dioxide and the positive electrode active material, thus suppressing the degradation of the positive electrode active material caused by high-temperature carbon dioxide.
[0168] The same procedure as in Reference Example 1 was followed to obtain a recycled positive electrode active material from the heated mixture. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were identical to those of the unused positive electrode active material. When the above-described coin-shaped battery was fabricated using the recycled positive electrode active material, and a charge-discharge test was conducted under the above conditions at 25°C, the discharge capacity was identical to that of a coin-shaped battery fabricated using the unused positive electrode active material.
[0169] (Example 3) The mixture before heating was obtained by operating in the same manner as in Reference Example 2. The obtained mixture before heating was placed in a continuous furnace, where it was heated while air was supplied in the opposite direction to the direction of travel of the mixture before heating. The maximum temperature in the continuous furnace was 450°C (below the melting start temperature of the activating agent), and the mixture before heating was heated under the condition of a residence time of 360 minutes in the continuous furnace. During this process, the carbon-containing materials (PVdF, acetylene black) contained in the mixture before heating generated carbon dioxide through heating, but this was removed from the heating furnace (continuous furnace) by supplying air. Therefore, if the concentration of carbon dioxide in the gas supplied to the heating furnace is compared with the concentration of carbon dioxide in the gas exhausted from the heating furnace, the concentration of carbon dioxide in the gas exhausted from the heating furnace is higher. By supplying air within the heating furnace, the contact between high-temperature carbon dioxide and the positive electrode active material can be suppressed, thus suppressing the degradation of the positive electrode active material caused by high-temperature carbon dioxide.
[0170] The same procedure as in Reference Example 2 was followed to obtain a recycled positive electrode active material from the heated mixture. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were identical to those of the unused positive electrode active material. When the above-described coin-shaped battery was fabricated using the recycled positive electrode active material, and a charge-discharge test was conducted under the above conditions at 25°C, the discharge capacity was identical to that of a coin-shaped battery fabricated using the unused positive electrode active material.
[0171] (Example 4) The mixture before heating was obtained by operating in the same manner as in Reference Example 2. The obtained mixture before heating and the carbon dioxide adsorbent were placed in an electric furnace. The mixture was heated in an air atmosphere at a temperature of 450°C (above the melting point of the activating agent) for 360 minutes. During this process, the carbon-containing materials (PVdF, acetylene black) in the mixture before heating generate carbon dioxide upon heating, but this carbon dioxide is removed from the furnace (electric furnace) by the carbon dioxide adsorbent. The carbon dioxide adsorbent inhibits the contact between high-temperature carbon dioxide and the positive electrode active material, thus suppressing the degradation of the positive electrode active material caused by high-temperature carbon dioxide.
[0172] The same procedure as in Reference Example 2 was followed to obtain a recycled positive electrode active material from the heated mixture. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were identical to those of the unused positive electrode active material. When the above-described coin-shaped battery was fabricated using the recycled positive electrode active material, and a charge-discharge test was conducted under the above conditions at 25°C, the discharge capacity was identical to that of a coin-shaped battery fabricated using the unused positive electrode active material.
Claims
1. A method for manufacturing a recyclable positive electrode active material, comprising the following steps: (1) A process of mixing a positive electrode composite containing a positive electrode active material and a carbon-containing material with an activating agent containing one or more alkali metal compounds to obtain a mixture; (2) The process of transferring the mixture into a heating furnace, heating the mixture while removing the carbon dioxide generated by heating the carbon-containing material from the heating furnace to obtain the heated mixture; (3) The process of recovering the heated positive electrode active material from the heated mixture.
2. The manufacturing method according to claim 1, wherein, The carbon dioxide is removed by blowing gas.
3. The manufacturing method according to claim 2, wherein, In the process (2), when the carbon dioxide concentration in the gas to be supplied to the heating furnace is compared with the carbon dioxide concentration in the gas exhausted from the heating furnace, the carbon dioxide concentration in the gas exhausted from the heating furnace is higher.
4. The manufacturing method according to any one of claims 1 to 3, wherein, The carbon dioxide is removed by passing it through a carbon dioxide adsorbent.
5. The manufacturing method according to any one of claims 1 to 3, wherein, In step (2), the mixture is heated to a temperature above the melting start temperature of the activating agent.
6. The manufacturing method according to any one of claims 1 to 3, wherein, In step (2), the mixture is heated to a temperature below the melting start temperature of the activating agent.
7. The manufacturing method according to any one of claims 1 to 3, wherein, The positive electrode active material contains lithium compounds.
8. The manufacturing method according to any one of claims 1 to 3, wherein, The positive electrode active material comprises a composite oxide containing at least one element selected from group 1 and at least one element selected from group 2. Group 1 elements: Ni, Co, Mn, Fe, Al, and P Group 2: Li, Na, K, Ca, Sr, Ba, and Mg.
9. The manufacturing method according to any one of claims 1 to 3, wherein, The activating agent comprises at least one compound selected from the group consisting of potassium compounds and sodium compounds.
Citation Information
Patent Citations
Method for recovering active material from discarded battery material
JP2012186150A